The Influence of Road Transport Infrastructure on Tourism Growth in Tanzania: A Case of Ruaha National Park - Zefania, Ligoha Samwel (AGUSPATI Research Institute, 2025)
This study assesses the influence of road transport infrastructure on tourism growth in Tanzania, focusing on Ruaha National Park. The main objectives were to assess the effects of road quality, accessibility, and networks on tourism growth. Adopting a positivist philosophy, a deductive approach, and a quantitative design, the research surveyed 353 tour operator companies, yielding 313 valid responses. Data were analyzed using descriptive and inferential statistics in SPSS. The findings indicate that road quality has a positive and statistically significant effect on tourism growth, demonstrating that improved road conditions enhance tourist access, satisfaction, and revenue generation. In contrast, road accessibility exhibited a negative but statistically insignificant relationship, implying that accessibility alone does not necessarily drive growth, possibly due to reliance on alternative transport modes and seasonal variations. However, road networks had a negative and statistically significant effect, suggesting that poorly integrated or misaligned networks can hinder tourist flows to Ruaha. Overall, the regression model was significant though it showed modest explanatory power. The study concludes that road quality is the most important determinant of tourism growth, while accessibility and networks require further contextual examination. Key recommendations include increased government investment in road maintenance and upgrading, stronger collaboration between Tanzania National Parks (TANAPA) and transport agencies to prioritize critical road sections, and greater involvement of tour operators in infrastructure feedback. It further calls for sustainable, strategically integrated road networks and future comparative research between northern and southern tourism circuits to inform balanced tourism policies.